Comparative evaluation of the use of bentonite and glauconitic clay on the structural and functional characteristics of rat liver with alcoholic hepatitis - Nasibullin, B. A.; Oleshko, A. YA.; Zmievskiy, A. V.; Baholdina, E. I.; Savitskiy, I. V. (Journal of Education, Health and Sport, 2015)
Nasibullin B A, Oleshko A Ya, Zmievskiy A B, Baholdina E I, Savitskiy I V. Сравнительная оценка результативности использования бентонитовых и глауконитовых глин на структурно-функциональные характеристики печени крыс с алкогольным гепатитом = Comparative evaluation of the use of bentonite and glauconitic clay on the structural and functional characteristics of rat liver with alcoholic hepatitis. Journal of Education, Health and Sport. 2015;5(2):165-172. ISSN 2391-8306. DOI: 10.5281/zenodo.15716 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A165-172 https://pbn.nauka.gov.pl/works/541802 http://dx.doi.org/10.5281/zenodo.15716 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. СРАВНИТЕЛЬНАЯ ОЦЕНКА РЕЗУЛЬТАТИВНОСТИ ИСПОЛЬЗОВАНИЯ БЕНТОНИТОВЫХ И ГЛАУКОНИТОВЫХ ГЛИН НА СТРУКТУРНО-ФУНКЦИОНАЛЬНЫЕ ХАРАКТЕРИСТИКИ ПЕЧЕНИ КРЫС С АЛКОГОЛЬНЫМ ГЕПАТИТОМ COMPARATIVE EVALUATION OF THE USE OF BENTONITE AND glauconitic clay on the structural and functional characteristics of rat liver with alcoholic hepatitis Б. А. Насибуллин, А. Я. Олешко, А. В. Змиевский, Е. И. Бахолдина, И. В. Савицкий B A Nasibullin, A Ya Oleshko, A B Zmievskiy, E I Baholdina, I V SaviTSkiy Украинский НИИ медицины транспорта, Одесса, Украина Ukrainian Research Institute for Medicine of Transport, Odessa, Ukraine Резюме Авторы в эксперименте на 43 белых крысах-самцах линии Вистар провели сравнительную оценку влияния бентонитовой и глауконитовой глин на развитие алкогольного гепатоза. Установлено, что внутренний прием 2,5 % взвеси обоих исследованных глин оказывал положительное, однонаправленное влияние на структурно-функциональную характеристику печени подопытных животных. Особенности влияния каждой из глин состоял в том, что бентонит сильнее влиял на процессы трансаминирования и репарации, а глауконитовые глины – на процессы энергообразования. Ключевые слова: глауконитовые глины, Бентонит, алкогольные гепатоз, печень. Abstract Authors in the experiment on 43 white male rats Wistar conducted a comparative assessment of the effect of bentonite clay and glauconitic to development alcoholic hepatosis. It was found that the inner reception 2.5% suspension of both studied clay has a positive impact on unidirectional structural and functional characteristics of the liver of experimental animals. Features of influence of each of the clays was that bentonite strongly influence the processes of transamination and repair, and glauconitic clay - the processes of energy production. Key words: glauconitic clay, bentonite, alcoholic hepatosis, liver.